Laundry Productivity Improvement Strategy with Objective Matrix (OMAX) and Analytical Hierarchy Process (AHP) Methods at PT Surabaya Laundry Sentosa - Mohammad Diki Setiawan; Hana Catur Wahyuni (Universitas Muhammadiyah Sidoarjo, 2022)
In increasing the productivity of the company, we do so not only by working harder but also by working smarter. The company's success in increasing productivity will greatly support its competitiveness in the market. This decrease can be seen in the product results of items whose laundry is not clean. The results of laundry that is less tidy can be seen in the results of laundry that usually can produce 2000 jeans per day but now can only produce 1500 jeans. There are five customers in the company, which are Emba Jeans, Lea Jeans, Hugo Jeans, Cardinal, and Lois. They are upset because the production process is taking longer and longer. The method used in this research is the integration of the objective matrix method and the analytical hierarchy process. The objective matrix method was chosen because it has a measurement system concept that combines several workgroup performance criteria in a matrix. The analytical hierarchy process was used because, with this method, existing problems are solved in an organized way, which can be shown to make effective decisions about the problem. From the results of the research, it is hoped that the improvement of the strategy will increase productivity with the Objective Matrix (OMAX) and Analytical Hierarchy Process (AHP) method used by the company to implement the method.